2019
DOI: 10.1002/jcb.28608
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of exogenous miR‐16 and miR‐34a on tumorigenesis of breast cancer cells

Abstract: Recent investigations have shown tumor-suppressive roles for miR-16 and miR-34a. They also share some features in regard to targeting cancer cell signaling pathways which they control. Therefore, in this study, we aimed to further scrutinize whether exogenous induction of mature miR-34a and miR-16 can collaborate in breast tumor suppression. MDA-MB-231 and SK-BR-3 human breast cancer cell lines were cultured and transfected twice with hsa-miR-16-5p and hsa-miR-34a-5p mimics individually or in combination. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
4
16
0
1
Order By: Relevance
“…Upregulation of β‐catenin expression in both MDA‐miR‐302/367 and SK‐miR‐302/367 cells by miR‐16 inhibitor indicates an important role for miR‐16 in regulation of β‐catenin in the BC cells. Suppression of vimentin and β‐catenin proteins by miR‐16 has previously been reported in oral squamous cell carcinoma, ovarian cancer cells, chordoma cells, and breast cancer cells by our group . MiR‐16 has been shown as an important suppressor of Wnt/β‐catenin signaling pathway, which targets WNT3A and Frizzled receptor gene, FZD6 , as two important factors of β‐catenin signaling cascade.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Upregulation of β‐catenin expression in both MDA‐miR‐302/367 and SK‐miR‐302/367 cells by miR‐16 inhibitor indicates an important role for miR‐16 in regulation of β‐catenin in the BC cells. Suppression of vimentin and β‐catenin proteins by miR‐16 has previously been reported in oral squamous cell carcinoma, ovarian cancer cells, chordoma cells, and breast cancer cells by our group . MiR‐16 has been shown as an important suppressor of Wnt/β‐catenin signaling pathway, which targets WNT3A and Frizzled receptor gene, FZD6 , as two important factors of β‐catenin signaling cascade.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, we showed that transfection of BC cells with miR‐302/367 cluster and miR‐16 mimic leads to downregulation of SMAD2 and upregulation of TGFBR2 . We previously showed that either miR‐16 or miR‐302/367 cluster can downregulate SMAD3 expression in MDA‐MB‐231 and SK‐BR‐3 cells . Bioinformatic analyses using several databases including TargetScan, miRTarBase, and TarBase and previous reports have shown that some TGF‐β signaling factors such as TGFBR3 , TGFB1 , SMAD2 , SMAD3 , SMURF1 , ACVR2a , and TGFBR2 are miR‐16 targets .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations